Novel insights into glucocorticoid replacement therapy for pediatric and adult adrenal insufficiency - Oprea, Alina; Bonnet, Nicolas C. G.; Pollé, Olivier; Lysy, Philippe A. (Therapeutic advances in endocrinology and metabolism, 2019)
Adrenal insufficiency is defined as impaired adrenocortical hormone synthesis. According to its source, the deficit is classified as primary (adrenal steroidogenesis impairment), secondary (pituitary adrenocorticotropic hormone deficit) or tertiary (hypothalamic corticotropin-releasing hormone deficit). The management of adrenal insufficiency resides primarily in physiological replacement of glucocorticoid secretion. Standard glucocorticoid therapy is shrouded in several controversies. Along the difficulties arising from the inability to accurately replicate the pulsatile circadian cortisol rhythm, come the uncertainties of dose adjustment and treatment monitoring (absence of reliable biomarkers). Furthermore, side effects of inadequate replacement significantly hinder the quality of life of patients. Therefore, transition to circadian hydrocortisone therapy gains prominence. Recent therapeutic advancements consist of oral hydrocortisone modified-release compounds (immediate, delayed and sustained absorption formulations) or continuous subcutaneous hydrocortisone infusion. In addition to illustrating the current knowledge on conventional glucocorticoid regimens, this review outlines the latest research outcomes. We also describe the management of pediatric patients and suggest a novel strategy for glucocorticoid replacement therapy in adults.